2001
DOI: 10.2466/pr0.2001.89.1.85
|View full text |Cite
|
Sign up to set email alerts
|

Reliability, Validity, and Factor Structure of the Arabic Version of the 12-Item General Health Questionnaire

Abstract: The aim was to examine the psychometric properties of the Arabic 12-item General Health Questionnaire in a sample of university students. A sample of 157 university students was screened using this questionnaire and the Hopkins Symptom Checklist-90. A standardized clinical interview using SCID was conducted on a subset of screened students. Reliability, validity, and factor analysis of the questionnaire were evaluated. Using factor score discrimination between cases and noncases was also evaluated. The Arabic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
78
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(97 citation statements)
references
References 26 publications
9
78
0
Order By: Relevance
“…These 3 factors explained 55% of the overall variance. Our findings were similar to that of previous factor analytic studies of GHQ-12 that have found three-factor solution [20,35,44]. In conformity, Martin and Newell [45] in their factor analysis of Graetz three-factor solution utilizing likert scoring revealed three factors: Anxiety, social dysfunction, and loss of confidence.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…These 3 factors explained 55% of the overall variance. Our findings were similar to that of previous factor analytic studies of GHQ-12 that have found three-factor solution [20,35,44]. In conformity, Martin and Newell [45] in their factor analysis of Graetz three-factor solution utilizing likert scoring revealed three factors: Anxiety, social dysfunction, and loss of confidence.…”
Section: Discussionsupporting
confidence: 90%
“…The findings were supported and verified by several other studies. Some of the research studies for example, Martin [44], and Daradkeh [20] revealed that the GHQ-12 was 3-dimensional, nonetheless, it utilized wide-ranging names from those proposed and used by Graetz [27]. In our study, factors designated as anxiety, social dysfunction, and loss of confidence, were subject to variation possibly due to being more under the influence of the socio-cultural norms and values that govern the population under study.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations